APPLICATIONS OF GENERALIZED SUMUDU TRANSFORM - CHINDHE, A.D. (Innovare Journal of Sciences, 2020)
Objective: To solve Cauchy Problem for the Wave Equation in One Dimensional Space using the generalized Sumudu transform. Materials and Methods: We use the new integral transform called the Sumudu transform for the extension to a generalized space and we use the method for extension followed by Zemanian[29]. Results and Conclusion: In this paper, I have established the application of generalized Sumudu transform. To illustrate the applications of generalized Sumudu transform, I have applied it to solve the cauchy problem for the wave equation in one dimensional space where the initial conditions are generalized functions.